2001
DOI: 10.1128/iai.69.11.7165-7168.2001
|View full text |Cite
|
Sign up to set email alerts
|

High-Level Expression of NRAMP1 in Peripheral Blood Cells and Tuberculous Granulomas fromMycobacterium bovis-Infected Bovines

Abstract: ByWestern blotting, we demonstrate high-level expression of NRAMP1 proteins in peripheral blood cells and granulomas of Mycobacterium bovis-infected bovines. Immunohistochemistry of granulomatous lesions showed heavily labeled epithelioid macrophages and Langhans cells. These data suggest that M. bovis infection enhances NRAMP1 expression and that active tuberculosis can occur despite this response.Mycobacterium bovis is the main causative agent of bovine tuberculosis (TB), a disease of great concern in develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…By Western blot, this antibody was shown to react with both the characteristic 65-kDa NRAMP1 band of J774 murine MØ activated with PMA and with a similar band in cattle PBMCs. 15 A monoclonal antiactin immunoglobulin G (IgG) antibody was purchased from Pierce (Rockford, IL). Polyclonal rabbit antibodies to iNOS and NT were obtained from Transduction Laboratories (Lexington, KY).…”
Section: Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…By Western blot, this antibody was shown to react with both the characteristic 65-kDa NRAMP1 band of J774 murine MØ activated with PMA and with a similar band in cattle PBMCs. 15 A monoclonal antiactin immunoglobulin G (IgG) antibody was purchased from Pierce (Rockford, IL). Polyclonal rabbit antibodies to iNOS and NT were obtained from Transduction Laboratories (Lexington, KY).…”
Section: Antibodiesmentioning
confidence: 99%
“…5,10 NRAMP1 is primarily expressed in MØs and tissues of the recticuloendothelial system, but its role in the resistance of or Vet Pathol 43: 709-717 (2006) susceptibility to mycobacterial infection remains undetermined. 3,4,35 In a recent study we demonstrated high expression of NRAMP1 in granulomas of M. bovis-infected cattle; 15 since granulomas are protective inflammatory reactions, 17,20,21 it was thought that NRAMP1 plays a defensive role against mycobacteria locally. This finding, in addition to recent studies showing a regulatory role for NRAMP1 in iNOS production, 2,18 prompted this study, which aims to analyze the expression of NRAMP1 and iNOS in M. bovis-infected cattle.…”
mentioning
confidence: 99%
“…Naturally resistant animals had the highest phagocytosis index and showed greater microbial control after exposure to M. bovis stimuli, producing stronger pro-inflammatory responses compared with susceptible animals [23]. In seeking to understand the reasons for natural variation in resistance, a high expression of NRAMP1 in peripheral blood cells and tuberculous granulomas from M. bovisinfected cattle appears to support a functional association for the SLC11A1 gene with enhanced protection against mycobacteria [5,23]. In bovines, two SLC11A1 alleles have been cloned and mapped to chromosome 2q43, which corresponds to a region predicted to encode a transmembrane polypeptide molecule that contains a conserved transporter motif and multiple phosphorylation sites [6,[13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…The host immune response to M. bovis infection is complex; following initial exposure, the bacilli are phagocytosed by host macrophages via transporters such as natural resistance-associated macrophage protein 1 (NRAMP1), encoded by the solute carrier family 11 member 1 (SLC11A1) gene. This transporter -which functions as part of the innate immune responseplays a key role in inhibiting proliferation of Mycobacterium tuberculosis (M. tuberculosis), through its involvement in acidification of phagosomes [5]. The relationships between various polymorphisms in the human SLC11A1 gene and mycobacterial diseases have been explored, including INT4 (single nucleotide G>C change in intron 4, 469+14G/C, rs3731865), D543N (conservative single base G>A substitution at codon 543, resulting in a change to asparagine from aspartic acid), and 3'UTR TGTG (a deletion in the 3' untranslated region, 1729+55del) [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Molecular genetics studies have focused on understanding host susceptibility and resistance factors such as innate, specific and regulatory immune response-related genes and their relationship to infectious pathogens. Allelic variants of several genes have been implicated in the genetic susceptibility to tuberculosis in some human populations, but little is known in cattle (Estrada-Chavez et al 2001).…”
mentioning
confidence: 99%